2015
DOI: 10.3892/or.2015.4435
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between expression of PD-L1 and PD-L2 on esophageal squamous cell carcinoma and the antitumor effects of CD8+ T cells

Abstract: Abstract. The programmed death-1 (PD-1)/programmed death-ligands (PD-Ls) signal pathway has been implicated as a potential immune escape mechanism in several human cancers. However, the studies of PD-1/PD-Ls pathway in esophageal squamous cell carcinoma (ECSS) are not yet sufficient. The current study investigated the expression of PD-L1, PD-L2 and PD-1 in ESCC tissues. The correlations between the expression of these proteins and clinical histopathological parameters were analyzed. Then the stable transfecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 50 publications
3
57
0
Order By: Relevance
“…The importance of PD-L1 in tumor development is demonstrated by its overexpression in a wide range of solid tumors. In ESCC, it has previously been reported that 18.9% to 79.7% of ESCC tumors are PD-L1 positive [21], [22], [23], [24], [25]. In this study, we demonstrate that 21% of the tumors are PD-L1 positive among the patients with ESCC in Hong Kong.…”
Section: Discussionsupporting
confidence: 57%
“…The importance of PD-L1 in tumor development is demonstrated by its overexpression in a wide range of solid tumors. In ESCC, it has previously been reported that 18.9% to 79.7% of ESCC tumors are PD-L1 positive [21], [22], [23], [24], [25]. In this study, we demonstrate that 21% of the tumors are PD-L1 positive among the patients with ESCC in Hong Kong.…”
Section: Discussionsupporting
confidence: 57%
“…In the present study, patients with PD‐L1 positive expression had significantly poorer prognosis than those with negative expression. A previous study reported that prognosis was not related to PD‐L2 expression in ESCC . Our previous study reported that among patients with high expression of HLA class I, high PD‐L1 expression was correlated with significantly poorer RFS and OS in ESCC .…”
Section: Discussionmentioning
confidence: 86%
“…[23][24][25][33][34][35][36][37][38][39][40] All these events are necessary to trigger antigen-specific CTLs (CD3 C CD8 C ), able to recognize and destroy tumor cells presenting altered and/or overexpressed molecular structures recognized as tumor-associated antigens. 41,42 On these bases, several studies in PC patients have investigated, with contrasting results, the prognostic role of the basal inflammatory status and lymphocytes density in the primary tumor. [43][44][45] However, all these studies are limited as they have been performed on elderly patients with bone metastases, who had undergone several years of hormonemanipulation and more or less severe prostate-cancer associated co-morbidities, all together potentially affecting the immune response.…”
Section: Discussionmentioning
confidence: 99%